How Reconnection-unfavored Magnetic Flux Emergence Suppresses Solar Filament Eruptions - Chengrui Zhou; Yuandeng Shen; Chun Xia; Hao Liang; Zehao Tang; Dongxu Liu; Surui Yao (The Astrophysical Journal Letters, 2025)
Magnetic flux emergence is traditionally considered to be a key trigger of solar filament eruptions, yet its role in suppressing filament eruptions remains less understood. Using multiwavelength observations from the Solar Dynamics Observatory, this study investigates a unique case of flux emergence below a quiescent filament from 2016 January 3 to 5, where the newly emerging magnetic flux suppressed rather than promoted the eruption of the filament. It is found that the emerging magnetic bipole within the filament channel directly interacted and reconnected with the overlying filament magnetic field and produced a series of two-sided coronal jets along the filament axis. Instead of eruption, the filament kept stable but broke into two segments at the reconnection site. Further magnetic cancellation or recession of the emerged bipole allowed the filament to recover its original structure. Our analysis results revealed that the flux emergence suppressed the filament eruption by reducing the upward net force. The formation and evolution of the filament fine structures (such as filament threads) are closely linked to the reconnection processes between the emerging bipole and the filament’s horizontal magnetic field. This study provides direct observational evidence for accounting for the stabilization of solar filaments driven by flux emergence, offering new insights into magnetic emergence’s dual role in triggering and suppressing solar eruptions.